First observation of optical gain on 5d–4f transitions of Ce3+ ions in up-conversionally pumped Ce3+, Pr3+:LiY0.3Lu0.7F4 mixed crystals. (23rd December 2015) - Gorieva, V G; Korableva, S L; Marisov, M A; Pavlov, V V; Semashko, V V
Abstract: The results of pump–probe experiments on the 5d–4f transitions of Ce 3+ ions in up-conversionally pumped Ce 3+, Pr 3+ :LiY0.3 Lu0.7 F4 crystals are presented and differential gain in the ultraviolet spectral range is demonstrated for the first time. The key parameters for the processes providing up-conversion pumping of the 5d states of Ce 3+ ions in Ce 3+, Pr 3+ :LiY0.3 Lu0.7 F4 mixed crystals via the 1 D2 level of Pr 3+ ions are estimated for the first time and the optimal pumping conditions are determined. The results of the pump–probe experiments and the mathematical modeling demonstrate that there are good prospects for the use of LiY0.3 Lu0.7 F4 :Ce 3+, Pr 3+ crystals as an active medium of solid-state tunable UV lasers with up-conversion pumping.